Prioritizing species, pathways, and sites to achieve conservation targets for biological invasion - McGeoch, Melodie A; Genovesi, Piero; Bellingham, Peter J; Costello, Mark J; McGrannachan, Chris; Sheppard, Andy (Biological invasions, 2016)
Prioritization is indispensable for the management of biological invasions, as recognized by the Convention on Biological Diversity, its current strategic plan, and specifically Aichi Target 9 that concerns invasive alien species. Here we provide an overview of the process, approaches and the data needs for prioritization for invasion policy and management, with the intention of informing and guiding efforts to address this target. Many prioritization schemes quantify impact and risk, from the pragmatic and action-focused to the data-demanding and science-based. Effective prioritization must consider not only invasive species and pathways (as mentioned in Aichi Target 9), but also which sites are most sensitive and susceptible to invasion (not made explicit in Aichi Target 9). Integrated prioritization across these foci may lead to future efficiencies in resource allocation for invasion management. Many countries face the challenge of prioritizing with little capacity and poor baseline data. We recommend a consultative, science-based process for prioritizing impacts based on species, pathways and sites, and outline the information needed by countries to achieve this. This should be integrated into a national process that incorporates a broad suite of social and economic criteria. Such a process is likely to be feasible for most countries.